The Relationship between Religion and Politics in Ibn Rushd's Philosophy - Robi Robi Sugara; Masykur Masykur; Iffan Ahmad Gufron; Wasehudin Wasehudin (Aqlania, 2026)
This study examines the relationship between religion and politics in Ibn Rushd’s philosophy as a response to perspectives that separate the two into mutually opposed domains. It employs a qualitative method based on library research and Gadamerian hermeneutic analysis. The primary data are drawn from Ibn Rushd’s works, especially Faṣl al-Maqāl fī mā Bayna al-Ḥikmah wa al-Sharī’ah min al-Ittiṣāl and al-Ḍarūrī fī al-Siyāsah. The study shows that the relationship between religion and politics in Ibn Rushd’s thought unfolds across three dimensions: ontological, epistemological, and axiological. Ontologically, religion and politics are rooted in the same source of truth, namely God as the First Cause and the Ultimate End. Epistemologically, religion provides the foundation of knowledge and morality, while politics actualizes these values in communal life. Axiologically, both are oriented toward the realization of justice, happiness, and human perfection. These findings affirm that Ibn Rushd’s thought offers a rational, ethical, and relevant paradigm for understanding the relationship between religion and politics in national and civic life.